Rozwiązanie Zagadnienia Cauchy’ego dla Równań Płaskiego Plastycznego Stanu Naprężenia za Pomocą Szeregów Potęgowych - Pielorz, A. (Engineering Transactions, 1967)
The state of stress is determined for perfectly plastic incompressible disc loaded on the edge. This edge is described by the natural analytic equation (3.1) and the load – by the analytic functions (3.4). A special set of curvilinear coordinates is used. The solution is obtained in the form of power series of the distance from the edge, the coefficients of the series being functions of the arch length of the edge. This is done for a disc, the edge of which is a circular arch the solution being shown to coincide with the existing solution of the same problem (cf. [1]). The results are particularly interesting in the neighbourhood of the edge.